PerfuzjaMethods of extracorporeal circulation in aortic aneurysms – our experience - Dmitruk-Sobiecka, Iwona; Hirnle, Tomasz; Adamczuk, Anna; Matlak, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Aortic dissection type A is a life-threatening condition and serious therapeutic problem. The procedure of choice is surgical treatment with the use of extracorporeal circulation. One method of cerebral protection, gaining more and more popularity, is selective cerebral perfusion. Based on our initial experience we present problems connected with conduction of ECC in a group of 10 patients in whom we applied antegrade selective cerebral perfusion. We present methods of cannulation and discuss parameters of ECC regarding selective cerebral perfusion. We present our remarks concerning the influence of appropriate site of arterial cannulation and technical problems with cannulation on conduction of effective ECC.